Brazil : Technical Assistance Report-Supporting Implementation of the Expenditure Rule Through Public Financial Management Reforms. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2017)
This Technical Assistance Report discusses the recommendations for supporting implementation of the expenditure rule through public financial management reforms in Brazil. To address rigidities in the budget and to create more fiscal space, authorities need to establish processes to build flexibility and improve efficiency. These include reviewing mandatory expenditures and indexation practices. Other options include a rolling program of spending reviews for large and fast-growing programs and efficiency dividends on ministries' operational expenses. Authorities also need to begin to develop a medium-term budget framework to support strategic decision making.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet